A macrossomia fetal e os níveis de glicemia plasmátic no TOTG com 75g de Dextrosol em gestantes : observação do estudo brasileiro de diabetes gestacional - Façanha, Cristina Figueiredo Sampaio (2004)
The relationship between maternal blood glucose and macrossomia has being an issue of controversy among different studies. In spite of the evidences that a linear and statistical significant association between maternal blood glucose and macrossomia do exists, no threshold glucose value has being identified as a major risk of this endpoint when using the 75g-OGTT in pregnancy. There are a lack of studies of statistical significance that clarify about the relationship between this test results and fetal growth. The aims of this study is to investigate the characteristics of maternal blood glucose on 75g – OGTT following the WHO criteria and an increased risk of large for gestational age infants in a cohort of 3942 woman from the Brazilian Study for Gestational Diabetes (EBDG,1991-1995). It has being the larger study about gestational diabetes that has being done in our Country and had validated the diagnostic of gestational Diabetes with the WHO criteria in relation to the endpoints such as macrosomia (SCHMIDT et al, 2001). A receiver-Operator characteristic (ROC) curve for the prediction of macrossomia were constructed for the feasting, one and two hours of 75-g glucose load values to determine the plasma glucose threshold value that yielded the highest combined sensitivity and specificity for the prediction of abnormal neonatal birth weight. An investigation about the proprieties of sensitivity and specificity of the cut points of glucose values on the test, distributed in terms of percentil was performed, and also these proprieties if having et least 1, et least two or the three values above certain percentil of the glucose values distribution. The results of these analyses had shown a statistical significant correlation between glucose values and macrossomia on the 75-g load ( p=0,000 ).The analyses of the TOTG-75g load values on ROC curve, with macrossomia as the end point , has shown no inflection point that discriminate a major risk of macrossomia. The discriminative power of the curve in fasting state, 1 hour and two hours is week , as shown by the area under the curve of 0,557 for fasting (CI: 527-588); 0,587 for 1hour values,( CI: 557-617): and 0,574 ( CI: 544-604) for 2 hours. Using the linear tendency test of Fleiss, (Fleiss, 1981) a constant increment on the incidence of macrossomia was observed, as the cut point of glycemia goes up on the range of the percentiles of distribution of glucose values, in such a way that do not exist a threshold level of glycemia that discriminate between an infant with macrossomia from other with adequate weight for gestational age. This study intends to contribute with its data for the discussions about sensible and specific criteria that define predictor’s end points in pregnancy.